CCAFS East Africa 2019–2021 Summary. Strategy for Supporting Agricultural Transformation, Food and Nutrition Security under Climate Change - Solomon, Dawit; Radeny, Maren A.O.; Mungai, Catherine; Recha, John W.M.; Schuetz, Tonya; Gadeberg, Marianne (2018)
Since the Maputo Declaration on Agriculture and Food Security in 2003, governments in East Africa have made sustainable transformation of agriculture a priority, as reflected in their development agendas and by increased investments in agriculture. Despite these positive developments, the region has seen very little improvement in food and nutrition security. Growth in the agricultural sector has primarily been achieved through unsustainable practices, such as increasing the total area of land under cultivation with very little improvement in productivity. The sector is still dominated by smallholder subsistence farmers, who are struggling with deep-rooted poverty and have few productive assets.1 Agricultural systems in the region also face environmental constraints to sustainable growth, such as degradation of soil, land, water and ecosystems. Additional challenges include economic barriers, low human and institutional capacities, poor agroadvisory services, political instability, conflicts and migration.1,2 Climate change and inter-annual climate variability compound these significant challenges to sustainable agricultural growth. Agriculture is not only impacted by climate change, but also contributes to climate change, necessitating both adaptation and mitigation strategies and actions. Agriculture is currently the main source of national greenhouse gas (GHG) emissions in East Africa, accounting for about 46% in Uganda and about 86% in Tanzania, for example. In the face of a changing climate, effective adaptation and mitigation strategies focusing on revitalization, intensification, diversification and innovation are thus needed to sustainably transform the region’s agriculture and decouple agricultural growth from GHG emissions.